1987
DOI: 10.1002/job.4030080406
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of burnout among public service lawyers

Abstract: Jon A. T u r n e r A r t h u r P . B r i e fLawyer Burnout A b s t r a c t S e v e r a l hypotheses suggested by t h e t h e o r e t i c a l l i t e r a t u r e on burnoutwere e m p i r i c a l l y t e s t e d i n an attempt t o i d e n t i f y t h e o r g a n i z a t i o n a l c o n d i t i o n s a s s o c i a t e d w i t h employee burnout. P u b l i c s e r v i c e lawyers i n t h e U.S. (rJ_= 3 9 1 ) completed a survey designed t o a s s e s s ( a ) t h r e e components of burnout, namely, emotional exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(119 citation statements)
references
References 15 publications
3
113
0
3
Order By: Relevance
“…A review of the relevant studies supports the latter alternative, suggesting a fairly consistent pattern in this regard. This pattern was found, for example, by Schwab and Iwanicki (1982) in a sample of school teachers; by Jackson, Turner and Brief (1987) in a sample of public service lawyers; and by Leiter and Maslach (1988) in a sample of nurses. In some studies, however, all three components were about equally aected (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…A review of the relevant studies supports the latter alternative, suggesting a fairly consistent pattern in this regard. This pattern was found, for example, by Schwab and Iwanicki (1982) in a sample of school teachers; by Jackson, Turner and Brief (1987) in a sample of public service lawyers; and by Leiter and Maslach (1988) in a sample of nurses. In some studies, however, all three components were about equally aected (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…Often referred to as 'compassion fatigue,' emotional exhaustion is believed to result from emotionally charged interactions with others. Depersonalization refers to the development of negative, cynical attitudes (Jackson, Turner, & Brief, 1987) about one's work, coworkers, and customers. Research suggests that employees experiencing depersonalization may withdraw from their work (Maslach & Pines, 1977).…”
Section: Three Components Of Burnoutmentioning
confidence: 99%
“…Research has shown that emotional exhaustion (a core dimension of burnout) is linked to reduced job satisfaction (Burke & Greenglass, 1995;Maslach & Jackson, 1986;Pines, Aronson, & Kafry, 1981;Wolpin, Burke, & Greenglass, 1991); reduced organizational commitment (Jackson, Turner, & Brief, 1986;Leiter & Maslach, 1988;Sethi, Barrier, & King, 2004); and high turnover and turnover intention (Firth & Britton, 1989;Jackson et al, 1986). The research literature suggests that technology professionals are particularly vulnerable to work exhaustion (Kalimo & Toppinen, 1995;Moore, 2000a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%